Gender equality as a component of the equality principle in society - Mashtalir, Khristina; Kapitan, Olha; Shai, Roman (Journal of Community Positive Practices, 2022)
In modern international realities, one of the most relevant and at the same time controversial topics remains gender equality between men and women, which means the legal principle and legal status of a person in relations with state authorities, which excludes discrimination based on gender. Gender equality thus reflects political and social changes in society. The relevance of the study is conditioned by the fact that one of the conditions for EU membership is to bring national legislation in line with European law, including compliance with legal procedures in the field of gender equality. Gender policy in society is the activity of numerous bodies and institutions of state power, which is aimed at achieving equality between men and women in all spheres of life, namely in the social, economic, and political spheres. Respect for the equality of all citizens is a mandatory requirement for EU membership. The purpose of the study is to analyse the institutional and regulatory aspect of the development of gender policy in modern society and determine the main trends in the development of the European gender balance policy in the world. Methods: the gender approach allows studying the political component of society and define such basic concepts as "gender policy", and "gender equality". Based on these fundamental concepts, an analysis of the political participation of men and women was conducted, comparing their roles and opportunities within the framework of European and Ukrainian legislation. The materials of the study are of practical value for the Ukrainian state in connection with the country’s chosen course towards European integration.